(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article studied the pores of dicyandiamide-formaldehyde resin based on dicyandiamide and formaldehyde. It was established that the study of the absorption of nitrogen vapor on samples of the DSDAF ion exchanger at a pressure of 0.950 P/P0 was 12.4811 cm3/g.